Women’s Awareness and Knowledge of Breast Self-Examination: A Study at the Obstetrics and Gynecology Teaching Hospital in Karbala City - Ismael Mohammed Alsaadi; Nada Khazal K. Hindi; Huda Mohammed Reda; Sarmad Salih Jawad; Noor Fadhil Al Maamouri; Rehab Flieh Hassan (Journal of Biomedicine and Biochemistry, 2025)
Breast cancer is the most frequent malignancy of women worldwide. The objective of this study is to explore the socio-demographic profiles of women attending the hospital and evaluate their understanding and awareness of breast self- examination practices. Methodology: A descriptive study design was employed at the Obstetrics and Gynecology Teaching Hospital in Karbala City. The study aimed to assess Women’s Awareness and Knowledge toward breast self- examination from 1st February 2024 to 1st February 2025. The study included a convenient sample of 100 women from the Obstetrics and Gynecology Teaching Hospital in Karbala City, specifically from the outpatient department. Result: The age distribution showed that most participants were between 20 and 26 years old, while fewer were in the older age categories. However, no significant association was found between age and breast cancer knowledge (p = 0.120). Regarding the age of first menarche, the majority of women experienced it at age 12 and again, no significant relationship was found with knowledge (p = 0.085). A highly significant correlation was observed between education level and knowledge (p = 0.001), with women holding higher education (39.0% with college and higher education) demonstrating better knowledge about breast cancer. Marital status also showed a significant association (p = 0.005), with single women making up the largest group (51.5%). Regarding occupation, a highly significant relationship was found (p = 0.001), with the majority of participants being housewives (40.0%), followed by government employees, private sector employees, and unskilled workers. Economic status also played a role, with 53.5% of women stating their economic situation was sufficient to some extent, and this factor had a significant impact on their knowledge (p = 0.05). Conclusion: Overall, education, marital status, occupation, economic status, menstrual history, and family history of breast cancer were key factors influencing women’s knowledge in this study.